Prevalence of Occlusal Morphological Patterns of Permanent Mandibular First Molar - B.Sushma1 , K. R. Don2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Teeth are informative indicators for the study of human populations, serving as markers and thebases for comparisons of genetic origin. Mandibular first molar is represented as 36 or 46 in the FDI system.The occlusal surfaces of posterior teeth occlude with the opposing occlusal surfaces of posterior teeth. Theocclusal morphology differs in each posterior tooth. The occlusal aspect of posterior teeth is developed intocusps ( 5 or 4 or 6 ) and grooves ( Y or + or X pattern ). These cuspal patterns and groove patterns help inforensic identification in cases like gender determination and also to identify the ethnic background of anindividual. Variation in degree of expression and frequency of teeth in dentitions of different populationsis different which may be helpful for forensic identification. The aim of the study was to determine theprevalence of different occlusal morphological patterns of permanent mandibular first molars. The studyincluded a predominantly South Indian population. Approval was received from the Institutional ReviewBoard. Study was conducted with 100 participants who were randomly selected. The occlusal morphologypatterns (number of cusps and groove pattern) of left and right permanent mandibular first molar wereassessed from the photographs of the oral cavity and the date was recorded. Results showed that the mostprevalent number of cusps in permanent mandibular first molar was 5 cusps ( 71% ) and Most prevalentgroove pattern in permanent mandibular first molar was Y pattern. It was also observed that the combinationof the 5Y pattern was more prominent in females than in males.